Proportion in school mathematics textbooks: A comparative study - Ponte, João Pedro da (2011)
This paper analyses how proportion is introduced and developed in selected mathematics textbooks for middle school students of Portugal, Spain, Brazil, and USA. The analysis focuses on the nature of the approach and on the cognitive demand, structure, and context of the tasks. The results show that the textbooks tend to present tasks at an intermediate level of cognitive demand and with a closed structure. Nonmathematical contexts predominate in three of the four textbooks. However, there are marked differences in the way textbooks approach the conceptual and procedural aspects of proportion. The way the students are addressed also varies, ranging from a questioning/problem solving style, to an explaining/practicing style, each of these styles supporting a rather different kind of activity.